Acute myeloid leukemia with adult atopic dermatitis as first manifestation: A case report. Issue 32 (August 2019) - Ma, Wei-Wei; Kasyanju Carrero, Lorna Martin; Yin, Xu-Feng; Liu, Hou-Fang; Zhou, Bing-Rong
Abstract: Rationale: Atopic dermatitis (AD) is a chronic recurrent dermatitis with profound itching, which could be the first manifestation of acute myeloid leukemia (AML). Patient concerns: A 53-year-old Chinese man suffered a 6-month history of systemic symmetrical dermatitis, accompanied with profound itching. The patient was diagnosed as "eczema" in several hospitals, and the effects of antihistamine and topical steroid creams were poor. Nocturnal sleep was seriously affected by aggravating pruritus. Laboratorial examination was compatible with AML-M4. Diagnoses: AML-M4 with AD as first manifestation. Interventions: IA regimen (ayninen and cytarabine) were used in induction chemotherapy. However, the patient did not achieve complete remission, and although his rash had improved, he still experienced severely general body itching. On the seventh day of chemotherapy, the patient entered the period of granulocyte deficiency with infection. Outcomes: The patient died due to septic shock after chemotherapy. Lessons: The case strengthens the awareness of AML with AD as first manifestation and raises oncological vigilance in patients with AD refractory.